2015
DOI: 10.5194/hess-19-3203-2015
|View full text |Cite
|
Sign up to set email alerts
|

Investigating temporal field sampling strategies for site-specific calibration of three soil moisture–neutron intensity parameterisation methods

Abstract: Abstract. The Cosmic-Ray Neutron Sensor (CRNS) can provide soil moisture information at scales relevant to hydrometeorological modelling applications. Site-specific calibration is needed to translate CRNS neutron intensities into sensor footprint average soil moisture contents. We investigated temporal sampling strategies for calibration of three CRNS parameterisations (modified N 0 , HMF, and COSMIC) by assessing the effects of the number of sampling days and soil wetness conditions on the performance of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 34 publications
3
30
0
Order By: Relevance
“…Thus they support the original hypothesis by Desilets et al (2010) of a single calibration campaign to capture the local soil moisture dynamics. The approach can thus substantially reduce the calibration efforts for CRNS probes, in contrast to recent findings from Iwema et al (2015) and Heidbüchel et al (2016).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus they support the original hypothesis by Desilets et al (2010) of a single calibration campaign to capture the local soil moisture dynamics. The approach can thus substantially reduce the calibration efforts for CRNS probes, in contrast to recent findings from Iwema et al (2015) and Heidbüchel et al (2016).…”
Section: Discussionmentioning
confidence: 97%
“…However, outstanding features were also reported in the CRNS data which did not fit well to the accepted theory described by Desilets et al (2010). Authors suggested that additional hydrological processes and hydrogen pools could influence the signal (e.g., Franz et al, 2013a;Baatz et al, 2014;Baroni and Oswald, 2015), while others applied recalibration of semiphysical parameters to better fit individual site conditions (e.g., Rivera Villarreyes et al, 2011;Lv et al, 2014;Iwema et al, 2015;Heidbüchel et al, 2016). Despite the unambiguous improvements obtained by corrections and recalibration approaches, some features in many datasets could still not be explained using current knowledge and consequently seemed to be unrelated to hydrological processes.…”
Section: Introductionmentioning
confidence: 94%
“…Moreover, given the small changes of 0 values for the 3 different calibration dates (±26 cph or 1.8% difference), we found the effects of vegetation on neutron count were likely small for this environment given the accuracy of the gravimetric calibration datasets themselves (standard error of mean ±0.02 m 3 /m 3 ). Finally, the recommendation of using a minimum of 3 calibration sampling dates at different water contents to estimate 0 was reported elsewhere [42] and is based on neutron particle transport modeling and an error propagation analysis. For best practices, we recommend a minimum of 3 gravimetric calibration periods to estimate 0 in agricultural environments.…”
Section: Temporal Variation Of Cosmic-ray Neutron Probe Soilmentioning
confidence: 99%
“…Soil bulk density, soil moisture, lattice water and 12 h averaged measured neutron intensity were used to determine calibration parameters specific to each CRNS and the COSMIC operator. This represents a compromise between the measurement noise (which follows a Poisson distribution) and the assumed variation of environmental variables over the averaging time window (Iwema et al, 2015).…”
Section: Site Description and Measurementsmentioning
confidence: 99%